Marked Improvement in Refractory TTP Directly after H. pylori Eradication Therapy - Irina Gringauz; Narin Nard Carmel-Neiderman; Tobin Mangel; Orith Portnoy; Gad Segal; Idan Goren (Case Reports in Hematology)
Thrombotic thrombocytopenic purpura (TTP) is a life-threatening disorder involving thrombotic microangiopathy and is characterized by increased platelet aggregation throughout the body. Acquired TTP can be triggered by a variety of conditions including infections. We hereby describe a case report of an 81-year-old female presenting to the internal medicine department with TTP and active chronic gastritis, positive for Helicobacter pylori (H. pylori) on biopsy. The TTP was highly resistant to medical therapy; however the patient underwent complete resolution of her TTP following H. pylori eradication. We conclude that acquired TTP may be triggered by H. pylori infection and that treating the underlying infection may play a role in improving TTP’s outcome in some patients, especially when disease is refractory to medical therapy.